UML is still inconsistent! How to improve OCL Constraints in the UML 2.3 Superstructure - Wilke, Claas; Demuth, Birgit (Electronic Communications of the EASST, 2011)
Since the first OMG specification of the Unified Modeling Language (UML), the Object Constraint Language (OCL) has been used for the definition of well-formedness rules in the UML specification. These rules have been specified within the early OCL years, when no appropriate tooling existed. Thus, they could not be checked for syntactical and static semantics correctness. In this paper we present an analysis of the static correctness of all OCL rules specified in the UML 2.3 superstructure document. We categorise found errors and propose changes for both the UML specification process and the OCL language to improve the UML specification’s correctness in future versions.